THE RHETORICAL MODEL OF IELTS SPEAKING TEST BAND 7 OR ABOVE - Warsidi, Warsidi; Damayanti, Neni; Syurganda, Andi (Universitas Muhammadiyah Metro, 2024)
Rhetorical studies in various texts have been widely conducted. However, compared to studies in written text, spoken text still received very little scholarly attention. For example, studies on rhetorical structure within the International English Language Testing System (IELTS) are hardly found in the literature. Responding to this fundamental need, this study intends to investigate what rhetorical model IELTS test takers employ to make their English-speaking receive excellent scores. This study analyzes ten IELTS speaking tests that receive band seven or above to realize this intention. These ten videos of IELTS speaking tests were taken from YouTube using standard criteria. Their recordings were transcribed to find their rhetorical model, and a top-down analytical approach was employed to find functional moves and strategies to achieve speakers' intentions. The results showed two communicative moves and six strategies as a rhetorical model used by the IELTS test takers who received band seven or above in the present study. This finding implies that understanding the rhetorical model of IELTS speaking may improve awareness of responding to interviewers' requests.